2022
DOI: 10.1111/gcb.16065
|View full text |Cite
|
Sign up to set email alerts
|

Where should China practice forestry in a warming world?

Abstract: As a nature‐based and cost‐effective solution, forestation plays a crucial role in combating global warming, biodiversity collapse, environmental degradation, and global well‐being. Although China is acknowledged as a global leader of forestation and has achieved considerable overall success in environmental improvements through mega‐forestation programs, many negative effects have also emerged at local scales due to the planting of maladapted tree species. To better help achieve carbon neutrality and the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 98 publications
3
40
0
Order By: Relevance
“…Therefore, planted forests in arid and semi-arid regions such as northwest China generally present low survival rates due to frequent drought events (Cao, 2008;Cao et al, 2011;F. Wang et al, 2020;Zhang et al, 2022). Although people try to improve the survival rate of trees by selecting an appropriate afforestation method, choosing proper tree species, and cooperating with a series of management measures, such as the application of fertilizer and irrigation, tending operations, etc.…”
Section: Effects Of Human Intervention On Forest C Sink Managementmentioning
confidence: 99%
“…Therefore, planted forests in arid and semi-arid regions such as northwest China generally present low survival rates due to frequent drought events (Cao, 2008;Cao et al, 2011;F. Wang et al, 2020;Zhang et al, 2022). Although people try to improve the survival rate of trees by selecting an appropriate afforestation method, choosing proper tree species, and cooperating with a series of management measures, such as the application of fertilizer and irrigation, tending operations, etc.…”
Section: Effects Of Human Intervention On Forest C Sink Managementmentioning
confidence: 99%
“…Similarly, a previous study reported that ecological restoration projects such as afforestation contributed more than half of the contribution to the enhancement of China's carbon stocks in project areas (Lu et al 2018). Moreover, the two monsoonal climatic regions are appropriate for potential afforestation (Zhang et al 2021). CO 2 had an effect equivalent to forest coverage in two monsoonal climatic regions but has a weaker contribution in the high-cold Tibetan Plateau with a high soil carbon sequestration potential as indicated by the relatively low Ratio sink .…”
Section: Influencing Factors Of Changes In China's Vegetation and Soi...mentioning
confidence: 80%
“…Given that the growth rate of planned forest coverage is relatively stable, we linearly extrapolated the planned forest coverage during 2035-2060 using trends over the past two decades. The planned forest coverage is less than the potential forest coverage in China reported by Zhang et al (2021). The green and orange columns in figure (c) are the predicted vegetation and soil carbon sinks in China under the forest coverage of the planned policies, respectively, assuming constant sensitivities (i.e.…”
Section: Influencing Factors Of Changes In China's Vegetation and Soi...mentioning
confidence: 99%
“…The GGP, started in 1999, is mainly applied to areas with serious soil erosion and to cultivated land with a slope above 25 degrees, involving vegetation restoration and conversion to forest [15,16]. It is the largest in scale and the longest in duration of all the projects in China, also affecting the largest population and attracting the largest amount of investment [17,18]. The GGP involves 2435 counties (including county-level units) in 25 provinces across the country.…”
Section: Introductionmentioning
confidence: 99%